2018
DOI: 10.21542/gcsp.2017.27
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kawasaki disease with emphasis on the echocardiographic profile: A single center experience

Abstract: Background: Echocardiographic features of acute Kawasaki disease (KD) have not been well characterized in Egyptian children. This study aimed to provide insight into the pattern of cardiac involvement in Egyptian children with Kawasaki disease, focusing on echocardiographic coronary abnormalities and their associated risk predictors.Methods and Results: Medical records of 64 KD patients from 2012 to 2016 were retrospectively analyzed with recalculation of coronary artery z-scores during the first eight weeks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
0
11
0
2
Order By: Relevance
“…Das complicações cardíacas em fase aguda mais graves destacaram-se três casos de disfunção ventricular esquerda, um com choque cardiogénico e um BAV de 1º grau, complicações essas também descritas na literatura. 2,7 Na fase aguda, foi ainda possível observar 10 pacientes com derrame pericárdico sem compromisso hemodinâmico e três com insuficiência valvular mitral ligeira. Em Paris, Chbeir et al 22 obtiveram relação estatisticamente significativa entre resistência à IGIV, AAC e achados na ecografia cardíaca inicial, tais como derrame pericárdico, hiperecogenicidade das coronárias e dilatação coronária.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Das complicações cardíacas em fase aguda mais graves destacaram-se três casos de disfunção ventricular esquerda, um com choque cardiogénico e um BAV de 1º grau, complicações essas também descritas na literatura. 2,7 Na fase aguda, foi ainda possível observar 10 pacientes com derrame pericárdico sem compromisso hemodinâmico e três com insuficiência valvular mitral ligeira. Em Paris, Chbeir et al 22 obtiveram relação estatisticamente significativa entre resistência à IGIV, AAC e achados na ecografia cardíaca inicial, tais como derrame pericárdico, hiperecogenicidade das coronárias e dilatação coronária.…”
Section: Discussionunclassified
“…2 Apesar de o envolvimento coronário ser a consequência mais temida da doença, são possíveis outras complicações cardíacas. 2,[6][7][8] O tratamento com imunoglobulina intravenosa (IGIV) na fase aguda continua a ser a principal terapêutica e, se administrada nos primeiros 10 dias de doença, diminui a incidência de AAC para 4%. 2 A resistência à IGIV ocorre em 10% a 20% dos casos, aumentado a probabilidade de envolvimento coronário.…”
Section: Introductionunclassified
“…meta-analysis was lower than our study. However, in the study of Hamza et al .,[ 19 ] the CAA incidence was 53.8%, and in Zhang's coherent study,[ 20 ] the incidence was 63.3%. Hence, Zhang's coherent trial had a higher CAA incidence than our study.…”
Section: Discussionmentioning
confidence: 99%
“…In Mexico, Garrido‐García et al 19 analysed the data of 508 KD patients and revealed that pericardial effusion was observed in 15% of patients, myocardial involvement occurred in 9.9% of patients, and electrographic abnormalities were present in 5.5% of patients. In Egypt, Hamza et al 20 retrospectively reviewed the medical records of 64 KD patients and found that endocardial dysfunction was identified in 8.5% of patients and pericardial effusion was detected in 7.8% of patients. During a 5‐year period (1998 to 2002), another prospective study from Shanghai, China, indicated that myocarditis and pericardial effusion were identified in 9% and 7% of 768 KD patients, respectively 21 .…”
Section: Discussionmentioning
confidence: 99%